Highly Porous NiFe Nanofoams Synthesized by Dynamic Hydrogen Bubble Template for Hydrogen Evolution in Alkaline Media - Gabriel Garcia Carvalho; Ricardo Espingardas do Nascimento; Maria Teresa Silva; Maria de Fátima Montemor (Small Structures)
When coupled with renewable energy sources, alkaline electrolysis (AEL) is a clean technology to produce hydrogen. The conventional electrodes that have been established as the commercial standard for AEL are perforated nickel plates, which have low surface area and high mass loads of active material. The use of Ni has been associated with the adsorption of protons and their recombination into H2 molecules, assisting and enabling the hydrogen evolution reactions. Due to the rising Ni price, there is a demand for less expensive electrode materials with identical, or better, performance. Thus, this work explores new alternative electrode materials and combines Ni with a cheaper and also electroactive metal, iron. For this purpose, highly porous bimetallic nanofoams are produced through the dynamic hydrogen bubble template. NiFe electrodes of different compositions are characterized by scanning electron microscopy, energy‐dispersive spectroscopy, linear sweep voltammetry, and chronopotentiometry analysis. The results allow obtaining key parameters that are essential for the optimization of the electrode's response considering overpotentials, Tafel slopes, and other electrochemically relevant parameters.